Highly Efficient Photocatalytic Anti‐Bacterial Ag Doped Titanium Dioxide Nanofilms with Combination of Reactive Oxygen Species and Ag Ions Releasing for Application of Vascular Implants. Issue 15 (15th July 2021) - Yao, Hang; Jiang, Lang; Luo, Xiao; Zou, Dan; Liu, Luying; Yang, Ping; Chen, Jiang; Zhao, Ansha; Huang, Nan
Abstract: Silver ions (Ag) as an effective biocidal metal has commercialized various anti‐bacterial materials. However, the high toxicity of Ag ions always induces undesired tissue injuries, impeding development on biomaterials. Recently, reactive oxygen species (ROS) emerges as the most promising agent for anti‐bacterial materials by modulating cell apoptosis. Herein, highly efficient anti‐bacterial Ag‐doped TiO2 nanofilms (TiO2 @Ag x, x  = 1, 2, 3) are reported wherein Ag ions and ROS are produced by controllable photocatalytic reaction upon UV irradiation, which mutually strengthens the anti‐bacterial efficiency to 99.7% (TiO2 @Ag2). Importantly, after doping amount screen of Ag ions, the TiO2 @Ag2 (Ag: 4.2%) nanofilm exhibits good hemocompatibility, synergistic suppression of smooth muscle cells proliferation with the combination of Ag ions and ROS, while having slight impacts on endothelial cells growth in vitro. Given these features, this nanofilm is applied on vascular stent which requires neointimal inhibition and re‐endothelialization healing for success of implantation. The 4‐weeks' implantation results reveal effective neointimal inhibition and rapid re‐endothelialization, indicating excellent biocompatibility as vascular stent. Abstract : A highly efficient photocatalytic anti‐bacterial Ag‐doped titanium dioxide nanofilm for surface modification of vascular stent exhibits strong neointimal inhibition and rapid re‐endothelialization by synergistically releasing reactive oxygen species and Ag ions, indicating great potentials in improving safety as well as efficiency profiles of stent in clinic and preventing from stent infection.